إدارة العلاقة مع الزبائن الالكترونية ومساهمتها في تعزيز ولاء الزبون -دراسة حالة مؤسسة موبيليس- - دويس علي; عباسي بوبكر (جامعة الوادي University of Eloued, 2024)
تهدف هذه الدراسة الى التعرف على الدور الذي تلعبه إدارة العلاقة مع الزبائن الالكترونية في تعزيز الولاء لدى زبون مؤسسة موبيليس وإبراز ذلك من خلال دراسة مدى تأثير الاتصال المباشر والرسالة الالكترونية والمعاملة التفضيلية في تحقيق ميزة تنافسية والعمل على تعزيز وزيادة ولاء الزبائن تجاه المؤسسة حيث تم جمع البيانات وتفسيرها باستخدام المنهج الوصفي التحليلي وذلك باستخدام استبانة موجهة لزبائن شركة موبيليس من أجل الإجابة على إشكالية الدراسية ، حيث خلصت الدراسة الى أن إدارة العلاقة مع الزبائن الالكترونية لها دور كبير في تعزيز ولاء الزبون This study aims to identify the role that electronic customer relationship management plays in enhancing loyalty among customers of the Mobilis Corporation and to highlight this by studying the extent to which direct communication, electronic messages, and preferential treatment influence achieving a competitive advantage and working to enhance and increase customer loyalty toward the organization, as it was done. Collecting and interpreting data using the descriptive analytical approach, using a questionnaire directed to customers of the Mobilis company, in order to answer the study’s problem. The study concluded that electronic customer relationship management has a major role in enhancing customer loyalty
Managing the relationship with electronic customers and its contribution to enhancing customer loyalty Mobilis case study
Keywords: إدارة العلاقة مع الزبائن، ولاء الزبون، اتصال مباشر، رسالة الكترونية، معاملة تفضيلية، مؤسسة موبيليس